2012
DOI: 10.1002/hipo.22004
|View full text |Cite
|
Sign up to set email alerts
|

Temporal manipulation of transferrin‐receptor‐1‐dependent iron uptake identifies a sensitive period in mouse hippocampal neurodevelopment

Abstract: Iron is a necessary substrate for neuronal function throughout the lifespan, but particularly during development. Early life iron deficiency (ID) in humans (late gestation through 2–3 years) results in persistent cognitive and behavioral abnormalities despite iron repletion. Animal models of early life ID generated using maternal dietary iron restriction also demonstrate persistent learning and memory deficits, suggesting a critical requirement for iron during hippocampal development. Precise definition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(140 citation statements)
references
References 50 publications
3
133
0
4
Order By: Relevance
“…In a previous study, murine hippocampal neurons expressing dominant negative Tfr1 had markedly decreased iron associated with altered dendrite structure and delayed GABAergic maturation, but the authors did not report an increase in cell death (10). Mice lacking IRP2 developed lower motor neuron degeneration, raising the possibility that a lack of utilizable iron can cause the death of some types of neurons (47).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In a previous study, murine hippocampal neurons expressing dominant negative Tfr1 had markedly decreased iron associated with altered dendrite structure and delayed GABAergic maturation, but the authors did not report an increase in cell death (10). Mice lacking IRP2 developed lower motor neuron degeneration, raising the possibility that a lack of utilizable iron can cause the death of some types of neurons (47).…”
Section: Resultsmentioning
confidence: 92%
“…It has been widely assumed that neuronal iron uptake depends on TFR1-mediated endocytosis of Fe 2 -TF (9), but in vivo evidence is scant. Expression of a dominant negative form of Tfr1 was shown to decrease iron uptake by hippocampal CA1 pyramidal neurons (10). However, others noted that iron distribution does not correlate with Tfr1 expression in the brain and suggested that Tfr1 may have roles unrelated to iron uptake (11).…”
mentioning
confidence: 99%
“…TFR is important for iron uptake (53). The expression of TfR mRNA was increased in the prefrontal cortex of MID and SID piglets, which may indicate the mechanism by which this brain region was able to maintain higher iron concentrations despite the piglets being fed deficient diets.…”
Section: Discussionmentioning
confidence: 97%
“…Mitochondrial enzymes, including cytochromes, NADPH, and flavoproteins, require iron in the form of heme and iron-sulfur clusters (9), which are integral for oxidative phosphorylation and ATP production. Iron status also regulates levels of BDNF and insulin-like growth factors and their receptors, which are primary regulators of neuronal growth and plasticity (6,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we examined the specific role of iron in developmental regulation of mTOR signaling using 2 unique genetic mouse models of in vivo neuronal ID that are not confounded by the hypoxia or increased uptake of other divalent metals that occur in dietary IDA (11,27). One model is generated by permanent, conditional Cre-lox P knockout of Slc11a2, the gene that codes for divalent metal transporter-1 (DMT-1) conditional knockout (DMT-1 CKO) in hippocampal neurons and results in a 40% decrease in the hippocampal iron concentration without affecting the remainder of the brain (27).…”
Section: Introductionmentioning
confidence: 99%